An investigation of intelligent search techniques for nurse scheduling improvement in healthcare organization - Mohd Rasip, Norhayati; Hasan Basari, Abd Samad; Ibrahim, Nuzulha Khilwani; Hussin, Burairah; Asmai, Siti Azirah (2013)
In healthcare organization, the primary objective of rostering is to plan and deploy the available skills and resources to best meet patient needs. This must be accomplishes with the aim to deliver high levels of staff satisfaction and worklife balance. The principle focus is to study the potential of Information Technology generally and Artificial Intelligence specifically to find the best solution for two specific problems in nurse rostering: shift design and satisfaction constraints problem. The challenges of nurse rostering problem are hard to modulate, heavily constrained, large search space and a large number of possible solution. Nurse rostering problem in real world is categorised as NP-hard. In this paper there have three parts. First section, a brief review about nurse demands and nurse rostering formulation. Second section, the recent related works in nurse rostering search technique in order to find a better exploitation and exploration of the search space nurse rostering problem and last section conclusion remarks from this investigation.